2006
DOI: 10.1007/s00192-006-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse repair by vaginal route using a new protected low-weight polypropylene mesh: 1-year functional and anatomical outcome in a prospective multicentre study

Abstract: The aim of this study was to evaluate the anatomical and functional results of a low-weight polypropylene mesh coated with an absorbable film in prolapse surgery by vaginal route. We have conducted a prospective multicentre study in 13 gynaecological and urological units. There were 230 patients requiring repair for anterior or posterior vaginal prolapse included. The present report is based on the analysis of the first 143 patients evaluated after at least 10 months follow-up. All patients were operated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1
22

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(90 citation statements)
references
References 19 publications
1
66
1
22
Order By: Relevance
“…In our study, no validated method was used in pre-and postoperative examination but the follow-up was 1 year, which is considered as a minimum adequate period of time to assess the efficacy of prolapse repair [22]. There have been reports of anatomically high success rates when meshes are used [10][11][12]16] and also significant improvements in the patients' quality of life have been reported [9]. Anatomical cure is naturally a remarkable indicator for outcome, especially when evaluating new surgical techniques for treating POP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, no validated method was used in pre-and postoperative examination but the follow-up was 1 year, which is considered as a minimum adequate period of time to assess the efficacy of prolapse repair [22]. There have been reports of anatomically high success rates when meshes are used [10][11][12]16] and also significant improvements in the patients' quality of life have been reported [9]. Anatomical cure is naturally a remarkable indicator for outcome, especially when evaluating new surgical techniques for treating POP.…”
Section: Discussionmentioning
confidence: 99%
“…The serious perioperative complication rates related to procedures using meshes in vaginal surgery have been low [11,12]. However, postoperative mesh-related adverse events, e.g., mesh erosion, may affect the quality of life in the long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…These include a poor healing environment, which is influenced by blood flow, infections, foreign body reactions, patient age, concomitant hysterectomy, and mesh characteristics. de Tayrac et al [19] reported that vaginal erosion occurred three times more often when a concomitant hysterectomy was performed. The authors explained that this difference was most likely due to vessel injury associated with uterine cervix dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with apical fixation or concomitant apical surgery [71][72][73][74][75][76][77][78][79], anterior repair using a synthetic mesh (excluding Prolift ® and Perigee ® ) had a cumulative success rate of 93 %; the cumulative success rate of studies without apical fixation or without standard apical surgery [80][81][82][83][84][85][86][87][88][89] was 83 %. The cumulative rate of mesh erosion was 8 % (137/1740); the cumulative rate for chronic pain and de novo dyspareunia was 7% (59/846).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%